A Half-Century Review of Library and Information Science Student Final Projects at Universitas Indonesia (1973–2022): A Bibliometric Analysis of Topics and Trends - Yasmidar, Nicky; Rahmi, Rahmi (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2025)
Bibliometric analysis provides valuable insights into the evolution, patterns, and distribution of research topics addressed in student final projects within the Department of Library and Information Science, Faculty of Humanities, Universitas Indonesia. This study investigates the development of these projects and the progression of research themes from 1973 to 2022, categorized into 20 thematic areas as outlined by Yelim Mo (2019). Using descriptive bibliometric methods, the study maps shifts in topic selection across five decades and identifies thematic areas that have emerged as dominant. The results indicate that topics related to library management, information user studies, collection management, records and archives management, and introductory studies in library and information science (LIS) appear most frequently. Conversely, areas such as introduction to information science, history of information and culture, metadata, and the history of libraries are notably underrepresented. Overall, the findings offer a comprehensive overview of research trends in library and information science at Universitas Indonesia and contribute to a broader understanding of knowledge production within the field. These insights have implications for curriculum refinement and future research planning, encouraging a more diverse and balanced distribution of themes in student scholarly work.